Consorting with Saints : Prayer for the Dead in Early Medieval France - McLaughlin, Megan (Cornell University Press, 2018)
In this book, Megan McLaughlin explores the social and cultural significance of prayer for the dead in the West Frankish realm from the late eighth century through the end of the eleventh century. She argues that the primary function of funerary and commemorative rituals in the early middle ages was to sustain the dead as members of the Christian community on earth, and to link them symbolically with the community of saints in heaven.